2018
DOI: 10.1159/000487294
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of High Gal-9 Expression in Solid Tumours: a Meta-Analysis

Abstract: Background/Aims: Recently, many studies have demonstrated that galectin-9 (Gal-9) exhibits altered expression and has a close association with metastasis and recurrence in various cancers. Therefore, we conducted a meta-analysis to assess the prognostic role of Gal-9 expression in solid tumours. Methods: We searched PubMed, Embase, and Web of Science until June 2017 and identified fourteen eligible studies containing 2,408 patients to include in the meta-analysis. Results: The pooled results indicated that hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
2
14
1
Order By: Relevance
“…Wang [20] suggested that galectin-3 plays an oncogenic role, and is expressed in colorectal cancer, non-small cell lung cancer and ovarian cancer. In addition, Wang [21] reported that high galectin-9 expression in cancer tissue was correlated with improved CSS (cancer-specific survival) and weakly improved OS or DFS/RFS in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Wang [20] suggested that galectin-3 plays an oncogenic role, and is expressed in colorectal cancer, non-small cell lung cancer and ovarian cancer. In addition, Wang [21] reported that high galectin-9 expression in cancer tissue was correlated with improved CSS (cancer-specific survival) and weakly improved OS or DFS/RFS in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two different study groups conducted similar meta-analyses in 2018 to explore the association of galectin-9 expression with prognosis in patients with solid tumors [ 14 , 15 ]. However, their conclusions were a bit different.…”
Section: Cancermentioning
confidence: 99%
“…However, their conclusions were a bit different. Wang K et al included 14 studies with 2408 patients up to June 2017, and demonstrated no significant association of high galectin-9 expression with OS (HR=0.80, P=0.311) or RFS/PFS (HR=0.58, P=0.097) in spite of its significant association with better CSS (HR=0.48, P<0.001) [ 14 ]. By contrast, Zhou X et al included 14 studies with 2326 patients up to October 2017, and reported a statistically significant association of high galectin-9 expression with better OS (HR=0.70, P=0.006), rather than DFS/RFS (HR=0.85, P=0.527) [ 15 ].…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to this goal, Gal-9 demonstrates anti-cancer effects in several tumor-bearing mouse models by either inducing apoptosis of cancer cells or activating immune cells such as dendritic cells, NK cells, and cytotoxic T cells [3][4][5][6]. Several retrospective studies clarified the positive correlations between Gal-9 expression in cancer tissues and improved patient prognosis in various cancer types [7]. These observations are inconsistent with the well documented immune suppressive function of Gal-9 and have revealed that Gal-9 biology is complex and poorly understood.…”
Section: Introductionmentioning
confidence: 99%